Covert Channel in RTP Payload Using a Pointer in SIP Header - Vozňák, Miroslav; Zbranek, Ivo; Mehic, Miralem; Komosný, Dan; Toral-Cruz, Homero; Chun-Wei Lin, Jerry (University of Zilina, 2016)
The paper addresses the issue of hiding data in the network flow. The authors discuss a new proposal of the steganographic approach in IP telephony: transmitting texts using the pointer in the SIP header by means of a data stream within the RTP protocol. This method is based on tagging the binary sequences in payload of the RTP packets, with the individual binary sequences representing individual steganogram characters. Subsequently, the position of the binary sequences is recorded in the SIP header in the Via field and the branch parameter. The proposed way of hidden data transmission cannot be detected by existing anomaly detectors; and does not represent an approach to statistical detection of covert channels. In fact, it is a new contribution to covert communication in ordinary VoIP traffic.

The paper addresses the issue of hiding data in the network flow. The authors discuss a new proposal of the steganographic approach in IP telephony: transmitting texts using the pointer in the SIP header by means of a data stream within the RTP protocol. This method is based on tagging the binary sequences in payload of the RTP packets, with the individual binary sequences representing individual steganogram characters. Subsequently, the position of the binary sequences is recorded in the SIP header in the Via field and the branch parameter. The proposed way of hidden data transmission cannot be detected by existing anomaly detectors; and does not represent an approach to statistical detection of covert channels. In fact, it is a new contribution to covert communication in ordinary VoIP traffic.
Covert Channel in RTP Payload Using a Pointer in SIP Header
Keywords: Steganography; VoIP; RTP; payload; SIP; pointer; Steganography; VoIP; RTP; payload; SIP; pointer